Towards empowering Gram Sabha - Aslam, M. (1999)
In order to revitalize grassroots democracy the Gram Sabha has to develop as an institution where common people can get an opportunity to participate in the process of self-governance. It is, therefore, essential to take necessary steps for creating conditions conducive for the process of self-governance to flourish at the grassroots level. These conditions may include the Gram Sabha for every village, periodic meetings, own procedure for conducting Gram Sabha, its business, authority to take up development programmes at the village level and participation of disadvantaged groups. - Reproduced
Keywords: Rural development - India; Panchayat